Безумное пари: роман / Татьяна Туринская - Туринская Татьяна (Русский Арлекин, 2007)
Экземпляры: ф16 (20171204) / Инвентарный номер: 55079 / Цена: 15.00 / Сис.шифр: Р2 / Авт.знак: Т 87 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6